Management of chickpea wilt through combination of fungicides and bioagents - and S.C. DUBEY*, R.K. PODDAR*, D.V. SINGH (Indian Phytopathology, 2004)
Amongst three isolates of Trichoderma harzianum from rhizosphere (TH-1) and non-rhizosphere (TH-2 and TH-3) soils of chickpea field, TH-1 exhibited highest antagonistic activity against Fusarium oxysporum f. sp. ciceri, causing wilt of chickpea (Cicer arietinum L.). Four systemic fungicides viz carbendazim, propiconazole, thiophanate-methyl and tebuconazole were evaluated and carbendazim caused maximum growth inhibition of the pathogen and supported maximum multiplication of Rhizobium ciceri in vitro. Four to eight fold increases in tolerance to carbendazim were developed in UV and Ã£-mutants of bioagent which showed enhanced antagonistic potential against the pathogen in vitro.